Assessing the test–retest repeatability of insulin resistance measures: Homeostasis model assessment 2 and oral glucose insulin sensitivity - Catherine A.P. Crofts; Mark C. Wheldon; Caryn Zinn; Xiaomiao Lan-Pidhainy; Thomas M.S. Wolever; Grant Schofield (Journal of Metabolic Health, 2017)
Background: Insulin resistance is commonly assessed using the homeostasis model assessment (HOMA) variants. HOMA is potentially insensitive to change because of its high coefficient of variation. The repeatability coefficient is an alternative means of assessing test repeatability. To be confident of clinical change, rather than biological variation, a subsequent test needs to differ from the former by more than the repeatability coefficient using the equation.